2018
DOI: 10.3389/fmicb.2018.01075
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomic, Proteomic, and Bioelectrochemical Characterization of an Exoelectrogen Geobacter soli Grown With Different Electron Acceptors

Abstract: The ability of Geobacter species to transfer electrons outside cells enables them to play an important role in biogeochemical and bioenergy processes. Our knowledge of the extracellular electron transfer (EET) process in the genus Geobacter is mainly from the study of G. sulfurreducens, and in order to fully investigate the EET mechanisms in the genus Geobacter, other Geobacter species should also be considered. This study focused on the EET of Geobacter soli GSS01, which exhibited a capability of reducing ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…In particular, constitutive expression has been reported for different terminal oxidoreductases of a thermophilic iron-reducer Melioribacter roseus from a deep subsurface aquifer ( Gavrilov et al, 2017 ), as well as for several multihemes involved in electron transfer to different electron acceptors in a mesophilic iron-reducing soil bacterium Geobacter soli ( Cai et al, 2018 ). A modular principle of the respiratory system organization, which implies differential activity of various multihemes, has been previously proposed for S. oneidensis ( Coursolle and Gralnick, 2010 ) and Geobacter species ( Butler et al, 2010 ; Aklujkar et al, 2013 ; Cai et al, 2018 ). However, the key proteins of the EET chain in C. ferrireducens differ significantly from their previously described counterparts of Geobacter , Shewanella , and Thermincola species ( Figure 7 and Supplementary Figure S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, constitutive expression has been reported for different terminal oxidoreductases of a thermophilic iron-reducer Melioribacter roseus from a deep subsurface aquifer ( Gavrilov et al, 2017 ), as well as for several multihemes involved in electron transfer to different electron acceptors in a mesophilic iron-reducing soil bacterium Geobacter soli ( Cai et al, 2018 ). A modular principle of the respiratory system organization, which implies differential activity of various multihemes, has been previously proposed for S. oneidensis ( Coursolle and Gralnick, 2010 ) and Geobacter species ( Butler et al, 2010 ; Aklujkar et al, 2013 ; Cai et al, 2018 ). However, the key proteins of the EET chain in C. ferrireducens differ significantly from their previously described counterparts of Geobacter , Shewanella , and Thermincola species ( Figure 7 and Supplementary Figure S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to most members of the genus Geobacter, all four strains can utilize both soluble and insoluble Fe(III) as the sole electron acceptor coupled with the oxidation of acetate, [25][26][27]53 and are capable of producing current on the anode of MFCs (Table 1). 11,26,54 3.2 Physiological comparison of Geobacter anodireducens to G. sulfurreducens and G. metallireducens Due to the in depth characterization and completed genome sequences of G. sulfurreducens PCA and G. metallireducens GS-15, further physiological comparisons with these species were done in order to uncover potential mechanisms used for enhanced EET in high salinity environments. As previous research has shown, G. anodireducens SD-1 grew fastest of the three strains with soluble Fe(III) citrate provided as the electron acceptor.…”
Section: Similarities To Geobacter Soli Gss01mentioning
confidence: 99%
“…Similar to other characterized Geobacter species, G. anodireducens appears to excel at its ability to exchange electrons with the extracellular environment. 26 Numerous studies have iden-tied c-type cytochromes that are involved in extracellular electron transfer to or from such substrates as Fe(III) oxide, Fe(III) citrate, Mn(IV) oxide, electrodes, Fe(0), Fe(III) containing sediments, and other microorganisms in such organisms as G. sulfurreducens, 33,37,[77][78][79] G. metallireducens, 32,40 G. soli, 54 and G. uraniireducens. 35 The G. anodireducens genome has 87 genes that could potentially code for c-type cytochrome proteins (ESI Table S2 †).…”
Section: Electron Transport Genes Involved In Extracellular Electron mentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological 78 properties of G. soli are different from those of G. sulfurreducens, and these 79 properties determine its special environmental significance, although both strains are 80 highly similar based on phylogenetic analysis (20). For example, G. soli can 81 anaerobically oxidize aromatic compounds, including phenol, benzoate and 82 benzaldehyde, while G. sulfurreducens cannot (20,21). In addition, G. soli has faster 83 Fe(III) oxide reduction and higher current production than G. sulfurreducens (Fig.…”
Section: Introductionmentioning
confidence: 99%